Structural basis for chromosome X-linked agammaglobulinemia: a tyrosine kinase disease. - Vihinen, M (1994)
X-linked agammaglobulinemia (XLA) is a hereditary defect of B-cell differentiation in man caused by deficiency of Bruton tyrosine kinase (BTK). A three-dimensional model for the BTK kinase domain, based on the core structure of cAMP-dependent protein kinase, was used to interpret the structural basis for disease in eight independent point mutations in patients with XLA. As Arg-525 of BTK has been thought to functionally substitute for a critical lysine residue in protein-serine kinases, the mutation Arg-525-->Gln was studied and found to abrogate the tyrosine kinase activity of BTK. All of the eight mutations (Lys-430-->Glu, Arg-520-->Glu, Arg-525-->Gln, Arg-562-->Pro, Ala-582-->Val, Glu-589-->Gly, Gly-594-->Glu, and Gly-613-->Asp) were located on one face of the BTK kinase domain, indicating structural clustering of functionally important residues.